Government policies for start-ups in Korea and its regions: Motives, mechanisms and major obstacles - Diana Schüler; Mihaela Suhalitca; Werner Pascha; Keun-yeob Oh (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2020)
The paper discusses the role of government policies and related support services in the formation of start-up businesses in South Korea. Start-ups can infuse an economy with renewed vigor, but it is questionable how Korea, an economy that has been dependent on a few large conglomerates in the past, can successfully encourage such start-up dynamism. The paper traces the economic history of start-ups and venture businesses in Korea and highlights its current situation. The analysis then focusses on explaining the start-up support policies, both on the level of central government and of the regions, paying attention to the intertwined role of the venture capital industry. A number of major obstacles are identified, in particular the ambiguous effects of social networks, the widespread risk aversion among potential entrepreneurs, the shortage of exit opportunities and the pronounced regional imbalances. The authors conclude that financial support measures should be streamlined, that the state should focus on creating appropriate framework conditions and that the regions should be given more independence from central government to choose their own path of development.
Keywords: M13; L26; L53; O38; R11; 330; South Korea; start-ups; start-up government policy; regional economic policy; venture capital industry